Migration and the elderly: Analyzing the social challenges of families left behind - Rahmanova, Gulchehra; Davlatova, Khulkaroy; Shahabitdinova, Shohida; Odiljonova, Aziza; Khayitova, Shakhnoza; Akhunov, Mukimjon (Edelweiss Applied Science and Technology, 2025)
Migration has emerged as one of the most transformative global phenomena of the 21st century, reshaping not only economies but also family structures and social dynamics. While much attention has been paid to the economic and labor market impacts of migration, far less is known about the effects on families left behind, particularly the elderly. This article delves into the myriad social challenges faced by elderly individuals whose children have migrated, often leaving them behind in vulnerable situations. These elderly parents, separated from their primary caregivers, frequently confront issues such as social isolation, emotional distress, financial instability, and disrupted family roles. Drawing from multiple disciplines—including sociology, economics, and gerontology—this article analyzes the intersection of migration and aging, with a particular focus on how migration-induced changes in family structure affect the elderly. Additionally, the paper explores the potential role of policy interventions and community-based solutions to mitigate these challenges. Ultimately, the study seeks to offer a comprehensive understanding of the social and emotional repercussions of migration on the elderly population, while providing recommendations to address these pressing issues in the context of modern global migration patterns.